Systematic Monetary Policy and the Macroeconomic Effects of Shifts in Loan-to-Value Ratios - Sebastian Rüth; Rüdiger Bachmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
What are the macroeconomic consequences of changes in residential mortgage market loan-to-value (LTV) ratios? In a structural VAR, real GDP and business investment increase significantly following an expansionary LTV shock. The impact on residential investment, however, is contingent on the systematic reaction of monetary policy. Historically, the FED responded directly to lower collateral requirements by significantly raising the policy instrument, thereby increasing mortgage rates and reducing residential investment. In a counterfactual policy experiment, where the Federal Funds rate remains constant after the shock, the reaction of non-residential GDP components is magnified and residential investment increases significantly. While firms increase their borrowing after a relaxation of bank lending standards, whether monetary policy reacts endogenously or is held constant, household debt only increases in an environment of a counterfactually constant Federal Funds rate.
Keywords: E30; E44; E52; 330